Corporate Social Responsibility :Academic Insights and Impacts - Idowu, Samuel O.; Vertigans, Stephen (London Spriger, 2017)
This book highlights the multi-faceted nature of corporate social responsibility and the need for greater engagement across academia to help develop the mechanisms needed to encourage socially responsible approaches across the board. The product of a cross-disciplinary collaboration of authors from various academic disciplines, the book reflects the emergent diversity of academics now studying corporate social responsibility (CSR). Accordingly, it includes contributions from economists to social anthropologists, from accountants to philosophers, and from clinical psychologists to social geographers. Together they provide new insights into aspects that challenge, hinder and enable CSR practitioners and corporations with regard to their financial impact and accountability, governance and supply chains. The book is divided into four parts focusing on the practical, sociological, theoretical and environmental aspects of corporate social responsibility.
Keywords: Economic sociology; Environmental management; Leadership; Marketing; Social responsibility of business; Corporate Social Responsibility; Business Strategy/Leadership.; Environmental Management; Marketing; Organizational Studies, Economic Sociology